Peran Etika Kristiani Dalam Pembentukan Karakter Mahasiswa Di Era Digital - Benedict Sandi Pangestu Rosa; Siti Haliza Zamili; Dwi Nina Putri Anakampun (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2026)
Abstract: The rapid development of digital technology has significantly influenced students’ lives, both academically and socially. Along with the ease of accessing information and communication, students are also confronted with various ethical challenges that may affect their character formation. This study aims to examine students’ understanding of Christian ethics, analyze its role in character formation, and explore the application of Christian ethical values in digital life. This research employed a quantitative method with a descriptive approach. Data were collected through a questionnaire distributed via Google Forms involving 50 Christian university students. The results indicate that students’ understanding of Christian ethics is categorized as very high. Most respondents reported applying Christian ethical values, such as honesty, responsibility, love, and discipline, in their digital activities. Furthermore, more than 90% of respondents agreed that Christian ethics plays a significant role in shaping students’ character in the digital era. Therefore, Christian ethics is proven to be relevant and contributes positively to the development of students’ character in responding wisely and responsibly to the challenges of digital life.   Keywords: Christian ethics, student character, digital era